John Dewey / His Contribution to the American Tradition - Edman Irwin (Greenwood Press, Publishers, 1968)
Introduction, Reconstruction in Philosophy, Philosophy as Education, Human Nature and Conduct, Intelligence and Inquiry, The Human Uses of Freedom, The Religion of Shared Experience, Democracy as a Moral Ideal, Index.
Introduction, Reconstruction in Philosophy, Philosophy as Education, Human Nature and Conduct, Intelligence and Inquiry, The Human Uses of Freedom, The Religion of Shared Experience, Democracy as a Moral Ideal, Index.